El liberalismo entendido como una perspectiva ética = Liberalism understood as an ethical perspective (2017)
One of the reasons why liberalism aspires to be a better form of political organization of society lies in the supposed impartiality of its normative principles as opposed to comprehensive positions of the good. This article follows Michael Sandel's critique of John Rawls' theory to show that a liberal society cannot avoid assuming ethical positions. To this end, some features of the debate between communitarianism and liberalism are addressed, problematizing the division between the moral and the political on which the latter defends its neutrality. From there, the discussion that Sandel engages with Rawls is extracted, objecting to the latter, that the concrete determination of rights in a liberal society cannot do without the discussion on values and ideas of a good life. Finally, some reflections are offered by way of conclusion